Music & the making of a new South - Campbell, Gavin James (African American music reference., 2004)
Startled by rapid social changes at the turn of the twentieth century, citizens of Atlanta wrestled with fears about the future of race relations, the shape of gender roles, the impact of social class, and the meaning of regional identity in a New South. Gavin James Campbell demonstrates how these anxieties were played out in Atlanta's popular musical entertainment. Examining the period from 1890 to 1925, Campbell focuses on three popular musical institutions: the New York Metropolitan Opera (which visited Atlanta each year), the Colored Music Festival, and the Georgia Old-Time Fiddlers' Conve.